Experiential Avoidance as a Mediator of the Relationship between Dispositional Mindfulness and Compulsive Sexual Behaviors among Men in Residential Substance Use Treatment. Issue 4 (2nd October 2017) - Brem, Meagan J.; Shorey, Ryan C.; Anderson, Scott; Stuart, Gregory L.
ABSTRACT: The present study sought to extend compulsive sexual behavior (CSB) and mindfulness research by testing whether dispositional mindfulness negatively related to CSB among men with substance use disorders (SUD) through experiential avoidance. Dispositional mindfulness is believed to decrease experiential avoidance, a correlate of CSB. We therefore hypothesized that dispositional mindfulness would relate to CSB indirectly through experiential avoidance. We reviewed medical records from 175 men in residential treatment for SUD. Results revealed significant indirect effects of dispositional mindfulness on CSB through experiential avoidance. Results provided preliminary support for developing mindfulness-based CSB interventions that target experiential avoidance.